Implementasi Kurikulum Merdeka Terhadap Kemampuan Berpikir Kritis Siswa SMAN 12 Bone - Reski Ana; Sahiruddin Sahiruddin; Syamsuria Syamsuria (Journal on Education, 2025)
This research is an ex post facto research with a quantitative approach which aims to determine the implementation of the independent curriculum on students' critical thinking abilities. The population of this study was 9 classes of class XI students at SMA Negeri 12 Bone with a random sample of 4 people each. The data collection technique in this research is observation and documentation by going directly to the research location. The data analysis technique uses Descriptive Analysis. The data is processed using validity tests in the form of questionnaires and reliability tests. Then to answer the research hypothesis using a simple linear regression formula and t test (partial). The results of the research show that the implementation of the Merdeka Curriculum has a positive effect on the critical thinking skills of students at SMA Negeri 12 Bone. This means that the H1 hypothesis is accepted, because the calculated t value > t table or 3.191 > 1.688 has a sig value of 0.000 < 0.05.